Hydrogel 3D printing with the capacitor edge effect - Wang, Jikun (Sci Adv, 2019)
Recent decades have seen intense developments of hydrogel applications for cell cultures, tissue engineering, soft robotics, and ionic devices. Advanced fabrication techniques for hydrogel structures are being developed to meet user-specified requirements. Existing hydrogel 3D printing techniques place substantial constraints on the physical and chemical properties of hydrogel precursors as well as the printed hydrogel structures. This study proposes a novel method for patterning liquids with a resolution of 100 μm by using the capacitor edge effect. We establish a complete hydrogel 3D printing system combining the patterning and stacking processes. This technique is applicable to a wide variety of hydrogels, overcoming the limitations of existing techniques. We demonstrate printed hydrogel structures including a hydrogel scaffold, a hydrogel composite that responds sensitively to temperature, and an ionic high-integrity hydrogel display device. The proposed technique offers great opportunities in rapid prototyping hydrogel devices using multiple compositions and complex geometries.